Modification of Prison Sanctions as an Effort to Overcome Overcapacity in Correctional Institutions in Indonesia: Modifikasi Sanksi Pidana Penjara Sebagai Upaya Mengatasi Overkapasitas dalam Lembaga Pemasyarakatan di Indonesia - Cameron, Calvin; Maskur, Muhammad Azil (Faculty of Law, Universitas Negeri Semarang, 2024)
Prison sentences remain one of the types of sanctions frequently imposed as a means of controlling criminal acts. This is due to the tendency to form criminal law regulations oriented towards punishment and sentencing, leading to over-criminalization, which in turn triggers overcapacity in correctional institutions, thus affecting the essence of the rehabilitation and reintegration process. This study employs a qualitative research approach with empirical research types. The data used consists of primary data sources, including interviews with officers from Semarang Class I Correctional Institution and judges from Semarang Class IA Special District Court, and secondary data sources, including legal regulations and scholarly publication materials such as journals, theses, dissertations, books, and legal dictionaries. The data collected is then processed, reduced, analyzed, and described descriptively. The research findings indicate that overcapacity occurs due to regulations and sentencing systems that tend to be oriented towards imprisonment. The prevalence of imposing prison sentences is also caused by extensive regulation within and outside the Criminal Code, combined with the law enforcement paradigm that views imprisonment as an obligation and the absence of sentencing guidelines. The overcapacity condition then triggers negative effects and the failure to fulfill the essence of rehabilitation and reintegration. Sanction modification efforts include reducing prison sentences through the application of weekend jail (intermittent sentencing); recovery and rehabilitation; judicial pardon; and the implementation of restorative justice.